Does Use of Text-to-Speech and Related Read-Aloud Tools Improve Reading Comprehension for Students With Reading Disabilities? A Meta-Analysis - Wood, Sarah G.; Moxley, Jerad H.; Tighe, Elizabeth L.; Wagner, Richard K. (Journal of learning disabilities, 2018)
Text-to-speech and related read-aloud tools are being widely implemented in an attempt to assist students’ reading comprehension skills. Read-aloud software, including text-to-speech, is used to translate written text into spoken text, enabling one to listen to written text while reading along. It is not clear how effective text-to-speech is at improving reading comprehension. This study addresses this gap in the research by conducting a meta-analysis on the effects of text-to-speech technology and related read-aloud tools on reading comprehension for students with reading difficulties. Random effects models yielded an average weighted effect size of ( d ¯ = .35, with a 95% confidence interval of .14 to .56, p < .01). Moderator effects of study design were found to explain some of the variance. Taken together, this suggests that text-to-speech technologies may assist students with reading comprehension. However, more studies are needed to further explore the moderating variables of text-to-speech and read-aloud tools’ effectiveness for improving reading comprehension. Implications and recommendations for future research are discussed.